In In-silico Identification of Potential Inhibitors of Human Dihydrouridine Synthase 2 for Cancer Therapy (Indian Journal of Pure & Applied Physics (IJPAP), 2023)
The formation of dihydrouridine from uridine substrate is catalysed by the human tRNA-dihydrouridine synthase (hDus2) enzyme. The abundance of dihydrouridine, possibly accumulated due to the aberrant function of hDus2, is linked with carcinogenesis. In this study, we focused on hDus2 enzyme, in hopes of discovering novel molecule with affinity for its tRNA binding site. Using the computational method, we performed virtual screening of a natural compound library (NPACT) with Autodock Vina, followed by validation using Smina and Idock. The top hits ZINC08219592, ZINC44387960, and ZINC95098958 were further investigated for their ADME properties to assess their potential as drug candidates. Additionally, the electronic structure properties of the lead molecules were investigated using Density Functional Theory (DFT). Our findings suggest that the identified natural molecules may act as potential hDus2 binders, opening new possibilities for the development of targeted anticancer drugs. This study provides a foundation for further research and the potential advancement of cancer therapeutics targeting on hDus2.